limx→0 (27+x)1/3−39−(27+x)2/3 is equal

limx0(27+x)1/339(27+x)2/3 is equal

  1. A

    -1/3

  2. B

    1/6

  3. C

    -1/6

  4. D

    1/3

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    We have, limx0(27+x)1/339(27+x)2/3

    =limx031+x271/31911+x272/3=limx01+x3×27+1311+2x3×27+=limx01[x/81]3[2x/81]=16

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.